IC 8285 Water Use In The Mineral Industry - With Appendix On The Projection Of Crude Material To 1985 By Barbara S. Lloyd - Alvin Kaufman (The National Institute for Occupational Safety and Health (NIOSH), 1966)
To aid industry and Government in planning water developments the Bureau of Mines in 1963 canvassed mineral producers to determine water use in 1962. Water use by the mineral industry comprises only 2 percent of the water withdrawn by industry as a whole. The major water-using mineral industries are natural gas processing, phosphate rock, sand and gravel, and iron ore. Analysis indicated the following conclusions: 1. Total water use and new water intake is dependent on the quantity of material processed and the process water requirements of the particular industry or commodity. 2. Recirculation is dependent on the processing requirements of a particular commodity, the manner in which the water is used, cooling and condensing requirements in certain large industries, the quality of new water intake, and the need to treat new and discharged water. 3. Consumed water is dependent on the quantity of water recirculated, the temperature and humidity in the area, and the proportion of water used for cooling and condensing. 4. A threefold increase in water use by the mineral industry by 1985 is forecast.